Improving the Quality of Public Services: Study of Implementation of Minimum Service Standards (SPM) - Safaruddin Safaruddin; Riskasari Riskasari; Masyitah Masyitah (Universitas Muhammadiyah Gorontalo, 2022)
In particular, when it comes to providing fundamental services to the populace, minimum service standards are well-positioned to address significant challenges in the implementation of regional or local administration. With actions chosen by the government, Minimum Service Standards (Generally known as SPM) implementation must ensure that the general public has access to essential services from regional or local governments. The goal of this research is to describe how SPM was used to raise the standard of public services in Coppo Tompong Village. The methodology in this study is qualitative. data gathering through observation, discussion, and documentation. Analyses of descriptive and qualitative data were employed. The study's findings indicate that while things have been going well, there is still room for improvement in terms of facilities and infrastructure due to poor management and budgetary allocations for unplanned natural catastrophes, including Covid-19. In accordance with the author's findings, more infrastructure and facilities need to be acquired in order to assist enhancing the quality of service in the Mandalle sub-district village of Coppo Tompong.